Analysis of the Implementation of the Independent Curriculum in Class IV Indonesian Language Subjects in State Elementary Schools 003 MERAL - Muhammad Rahmat; Tisrin Maulina Dewi; Zulfiana Sessyka Putri (Indonesian Journal of Primary Education, 2024)
Muhammad Rahmat. Analysis of the Implementation of the Independent Curriculum in Indonesian Language Learning for Grade IV at SD Negeri 003 Meral. Department/Study Program of Elementary School Teacher Education, Faculty of Teacher Training and Education, University of Karimun, 2024. This study aims to describe: 1) to analyze the implementation of the independent curriculum in Indonesian language learning for Grade IV at SD Negeri 003 Meral, 2) to analyze the obstacles and challenges in implementing the independent curriculum in Indonesian language learning for Grade IV at SD Negeri 003 Meral, 3) to analyze the efforts to overcome obstacles and challenges in implementing the independent curriculum in Indonesian language learning for Grade IV at SD Negeri 003 Meral.  This research is qualitative research. The study was conducted at SD Negeri 003 Meral in April 2024. The subjects of this research are the Principal, Grade IV Teachers, and Grade IV Students. Data collection techniques were carried out using observation, interviews, and documentation. Activities in qualitative data analysis used an interactive model, namely data collection, data reduction, data display, and conclusion drawing.  The results of this study indicate that: 1) the implementation of the independent curriculum in Indonesian language learning has been well realized, the planning carried out includes analyzing learning objectives, preparing lesson plans, and creating learning activity programs. The implementation of learning has already applied differentiated learning tailored to students' needs and has designed evaluations in the form of diagnostic, formative, and summative assessments, 2) there are obstacles and challenges such as lack of information, limited reference sources, and time constraints in the preparation of teaching modules and assessments, 3) efforts made to overcome obstacles and challenges include participating in seminars, webinars, and workshops, increasing reference sources, and utilizing the teaching module preparation guidelines provided by the government.